Tensions in Corporate Sustainability: Towards an Integrative Framework - Hahn, Tobias; Pinkse, Jonatan; Preuss, Lutz; Figge, Frank (Journal of business ethics, 2015)
This paper proposes a systematic framework for the analysis of tensions in corporate sustainability. The framework is based on the emerging integrative view on corporate sustainability, which stresses the need for a simultaneous integration of economic, environmental and social dimensions without, a priori, emphasising one over any other. The integrative view presupposes that firms need to accept tensions in corporate sustainability and pursue different sustainability aspects simultaneously even if they seem to contradict each other. The framework proposed in this paper goes beyond the traditional triad of economic, environmental and social dimensions and argues that tensions in corporate sustainability occur between different levels, in change processes and within a temporal and spatial context. The framework provides vital groundwork for managing tensions in corporate sustainability based on paradox strategies. The paper then applies the framework to identify and characterise four selected tensions and illustrates how key approaches from the literature on strategic contradictions, tensions and paradoxes—i.e., acceptance and resolution strategies—can be used to manage these tensions. Thereby, it refines the emerging literature on the integrative view for the management of tensions in corporate sustainability. The framework also provides managers with a better understanding of tensions in corporate sustainability and enables them to embrace these tensions in their decision making.